Relationship between knowledge and reproductive health attitudes with early marriage at gowa regency high school - Nita, Nur Rahma; Azis, Andi Asmawati; Adnan, Adnan (JPBIO (Jurnal Pendidikan Biologi), 2024)
This research is important to carry out to provide information, knowledge, and understanding regarding adolescent reproductive health topics. This study aims to determine the relationship between knowledge and attitudes about reproductive health and early marriage among teenagers in Gowa Regency High School. The population of this study was all class XI at SMA Gowa Regency. The sampling technique was carried out using the simple random sampling technique. This type of research is descriptive correlational research which aims to determine whether there is a relationship between variables. This research design uses a cross-sectional study design. The research instruments used were tests and questionnaires, data collection techniques in multiple-choice questions to measure reproductive health knowledge, and a questionnaire that refers to Likert scale parameters to measure attitudes towards reproductive health and early marriage. This research data analysis technique uses descriptive and inferential data analysis techniques. There is a relationship between knowledge and Reproductive health attitudes and early marriage are significant with a correlation value (R) between variables was 0.789 which is included in the strong correlation category.